Effect of amyloid-beta peptides on astrocytic Ca2+ signaling and gliotransmission: modulation by adenosine A2A receptors - Dias, Liliana Rodrigues (2018)
Dissertação de Mestrado em Bioquímica apresentada à Faculdade de Ciências e Tecnologia